A novel sorting technology allows for highly efficient selection of sperm without chromatin damage. (June 2013) - Funaro, Michael G.; Kim, Howard H.; Mazel, Svetlana; Bolyakov, Alexander; Goldstein, Marc; Schlegel, Peter N.; Paduch, Darius A.
<x xml:space="preserve">Abstract</x> Sperm chromatin damage has been associated with male infertility, increased risk for spontaneous abortion, and poor embryo development. Available methods for detecting chromatin damage render the sperm no longer suitable for clinical use. Early apoptotic events resulting in chromatin damage are associated with increased permeability of the cell membrane to large ions. We propose the use of a large fluorescent organic cation, proprietary fluorochrome (PF-1), for fluorescence-activated cell sorting (FACS) for negative selection of sperm without chromatin damage. Sperm with chromatin damage are PF-1 positive. Performance of cell sorting by PF-1 was verified with terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) after FACS on PF-1(+) and PF-1(-) subpopulations. Whereas 19.5% of PF-1 positive sperm were TUNEL positive only 1.5% sperm in the PF-1(-) fraction were TUNEL positive (p < 0.00001). TUNEL values below 1.9% were considered background fluorescence. Post-sorting motility and vitality were 49.4% (SD: 12.5) and 65.0% (SD: 14.99), respectively. Proprietary fluorochrome activated sperm sorting may decrease or most likely eliminate all of TUNEL positive sperm without adverse effects on viability, providing a new therapeutic avenue for men with a high percentage of TUNEL positive sperm. Further research is needed to determine if the reduction in TUNEL positive sperm using PF-1 will improve in vitro fertilization (IVF) outcomes.